Controllable assembly of rectangular macrocycles bearing different numbers of unsaturated sites based on half-sandwich iridium fragments. Issue 18 (24th April 2018) - Dang, Li-Long; Lin, Yue-Jian; Jin, Guo-Xin
Abstract : Three novel rectangular metallacycles without unsaturated metal sites and with one or two unsaturated metal sites have been constructed from pyrazine-2, 3-diamine and/or 2, 3-dihydroxy-quinoxaline proligands. Abstract : A series of hexanuclear rectangular macrocycles were designed and synthesized by utilizing multifunctional pyrazine-derived (pyrazine-2, 3-diamine (H4 L 1 )) and quinoxaline-derived ligands (2, 3-dihydroxy-quinoxaline (H2 L 2 )) featuring two monodentate sites and one pair of chelating sites. X-ray crystallography in combination with 1 H NMR spectroscopy elucidated that both half-sandwich iridium diimine and dihydroxy moieties are located on either side of the rectangular macrocycles, making them centrosymmetric. Thereby, the prepared diimine-functionalised complexes were found to have unsaturated metal sites on account of their strongly bound Ir–N–C–C–N arrangement. However, all the iridium atoms in the rectangular macrocycles containing dihydroxy groups were found to adopt an 18-electron coordination configuration, indicating that the O, O′-bonded iridium centers had bound additional ligands, such as Cl −, MeOH, MeCN, etc. Notably, a rare rectangular macrocycle containing a single coordinatively unsaturated metal site was achieved when the ligands H2 L 1 2 − and L 2 2 − were introduced simultaneously.